Minimisation of dissipated energy in the airways during mechanical ventilation by using constant inspiratory and expiratory flows – Flow-controlled ventilation (FCV). (December 2018) - Barnes, Tom; van Asseldonk, Dirk; Enk, Dietmar
Abstract: It has been suggested that energy dissipation in the airways during mechanical ventilation is associated with an increased probability of ventilator induced lung injury (VILI). We hypothesise that energy dissipation in the airways may be minimised by ventilating with constant flow during both the inspiration and expiration phases of the respiratory cycle. We present a simple analysis and numerical calculations that support our hypothesis and show that for ventilation with minimum dissipated energy not only should the flows during inspiration and expiration be controlled to be constant and continuous, but the ventilation should also be undertaken with an I:E ratio that is close to 1:1.